Protein tyrosine phosphatase PTPRJ is negatively regulated by microRNA‐328. (30th May 2012) - Paduano, Francesco; Dattilo, Vincenzo; Narciso, Domenico; Bilotta, Anna; Gaudio, Eugenio; Menniti, Miranda; Agosti, Valter; Palmieri, Camillo; Perrotti, Nicola; Fusco, Alfredo; Trapasso, Francesco; Iuliano, Rodolfo
<x xml:space="preserve">Abstract</x> Expression of PTPRJ, which is a ubiquitous receptor‐type protein tyrosine phosphatase, is significantly reduced in a vast majority of human epithelial cancers and cancer cell lines (i.e. colon, lung, thyroid, mammary and pancreatic tumours). A possible role for microRNAs (miRNAs) in the negative regulation of PTPRJ expression has never been investigated. In this study, we show that overexpression of microRNA‐328 (miR‐328) decreases PTPRJ expression in HeLa and SKBr3 cells. Further investigations demonstrate that miR‐328 acts directly on the 3′UTR of PTPRJ, resulting in reduced mRNA levels. Luciferase assay and site‐specific mutagenesis were used to identify a functional miRNA response element in the 3′UTR of PTPRJ. Expression of miR‐328 significantly enhances cell proliferation in HeLa and SKBr3 cells, similar to the effects of downregulation of PTPRJ with small interfering RNA. Additionally, in HeLa cells, the proliferative effect of miR‐328 was not observed when PTPRJ was silenced with small interfering RNA; conversely, restoration of PTPRJ expression in miR‐328‐overexpressing cells abolished the proliferative activity of miR‐328. In conclusion, we report the identification of miR‐328 as an important player in the regulation of PTPRJ expression, and we propose that the interaction of miR‐328 with PTPRJ is responsible for miR‐328‐dependent increase of epithelial cell proliferation.